1973
DOI: 10.1055/s-0038-1649131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroids upon Fibrinogen Metabolism in Rabbits

Abstract: SummaryThe effect of pharmacologic doses of adrenal corticosteroids upon plasma fibrinogen level, incorporation of 75Se-Methionine (75SeM) into fibrinogen, and disappearance of plasma 125I-fibrinogen was evaluated in rabbits. Single 25 mg doses of hydrocortisone or cortisone transiently increased both 75SeM incorporation into fibrinogen and plasma fibrinogen levels, but 1 to 5 mg doses of hydrocortisone had no significant effect upon plasma fibrinogen levels. Repeated daily injections of 25 mg of hydrocortison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the rabbits, both ACTH preparations induced similar elevations in plasma fibrinogen and fibronectin, despite a difference in the extent and duration of the induced increase in plasma corticosterone values. The administration of pharmacological doses of corticosteroids to rabbits can increase the incorporation of [ 5Se]-methionine into fibrinogen and elevate plasma fibrinogen values (Seligsohn et al, 1973b). However, the effect of corticosteroids on fibrinogen metabolism in the rabbit is partly influenced by the presence or absence of a coexistent inflammatory stimulus (Seligsohn et al, 1973b), suggesting that, in this species also, other factors are also involved in the regulation of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rabbits, both ACTH preparations induced similar elevations in plasma fibrinogen and fibronectin, despite a difference in the extent and duration of the induced increase in plasma corticosterone values. The administration of pharmacological doses of corticosteroids to rabbits can increase the incorporation of [ 5Se]-methionine into fibrinogen and elevate plasma fibrinogen values (Seligsohn et al, 1973b). However, the effect of corticosteroids on fibrinogen metabolism in the rabbit is partly influenced by the presence or absence of a coexistent inflammatory stimulus (Seligsohn et al, 1973b), suggesting that, in this species also, other factors are also involved in the regulation of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of pharmacological doses of corticosteroids to rabbits can increase the incorporation of [ 5Se]-methionine into fibrinogen and elevate plasma fibrinogen values (Seligsohn et al, 1973b). However, the effect of corticosteroids on fibrinogen metabolism in the rabbit is partly influenced by the presence or absence of a coexistent inflammatory stimulus (Seligsohn et al, 1973b), suggesting that, in this species also, other factors are also involved in the regulation of fibrinogen. It has also been shown that, while the administration of dexamethasone to rabbits can induce a similar increase in fibrinogen and fibronectin, it is less effective than ACTH (Lichen, 1988;Licheng and Gentry, 1991).…”
Section: Discussionmentioning
confidence: 99%